A tributação ambiental como instrumento de proteção ambiental: um estudo de caso da experiência do ICMS ecológico no Estado do Paraná - Zachow, Pamera Emanuele Riegel (2017)
Environmental taxation is a extrafiscal function instrument being used to encourage behaviors that are consistent with the preservation of the environment. In turn, the Ecological ICMS is an environmental protection tool and has shown effective results in the induction of the municipalities to adopt environmental protection policies. The Federal Constitution of Brazil states that it is the duty of the community, municipalities, states and the EU find ways to address environmental problems and adhere to mechanisms that allow an improvement in the environment, thus ensuring an ecologically balanced environment for future generations. In this sense, the general objective of this research was to present, through a bibliographical and documentary research, the evolution of the Ecological ICMS in the State of Paraná, demonstrating the relevance of environmental taxation as an environmental preservation mechanism. To achieve the general objective, the following specific objectives were outlined: a) Analyze the importance of environmental tax legislation; B) Verify that the Ecological ICMS law contributes to the protection of the environment; C) Examine the growth of municipalities benefiting from the Ecological ICMS; D) Examine whether the areas of environmental protection have grown. To do so, the bibliographic survey led this study to the following assumptions: a) Ecological ICMS can be considered as an incentive element for the preservation of the environment. The state governments, through specific legislation, have allowed the emergence of new areas of preservation, as well as maintaining and strengthening the protection of existing areas and b) Considering the importance of the maintenance of native areas, as well as the importance of the existence of Conservation Units, it is perceived that the Ecological ICMS has a fundamental role when it comes to financial compensation to municipalities that maintains environmental conservation areas.